Total of Escherichia coli Excreta Broiler Given Enterococcus sp. as Probiotics Candidate of Poultry - Muhammad Nur Hidayat; Khaerani Kiramang; Felis Gunawan (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2019)
The purpose of this study was to see the effect of giving Enterococcus sp. bacteria at Escherichia coli of excreta broiler. The research design used was a completely randomized design consisting of four treatments, three replications, and each replication had four broilers. The treatment given consisted of T1 (0 mL/L), T2 (1 mL/L), T3 (3 mL/L), and T4 (5 mL/L) control treatments. The number of colonies of Enterococcus sp. given through drinking water every day, namely 107 CFU / mL. The results of the study respectively showed the number of Escherichia coli in the treatment of T1 (Log 7.54 CFU/g), T2 (Log 7.53 CFU/g), T3 (Log 7.48 CFU/g), and T4 (Log 6.78 CFU/g). The colony total of Escherichia coli of broiler excreta decreases with increasing doses of Enterococcus sp. It is shown that Enterococcus sp. has an antimicrobial compound activity which can inhibit pathogen growth in broiler digestive tract so that it has the potential to be developed as a probiotic